Self-Medication in Europe: Economic and Social Impact on Individuals and Society - May, Uwe; Bauer, Cosima; Schneider-Ziebe, Anissa; Giulini-Limbach, Chiara (Gesundheitsökonomie & Qualitätsmanagement, 2023)
Objectives To demonstrate the different monetary and time-related costs associated with the treatment of minor ailments (MAs) in the case of a general practitioner (GP) visit or self-medication with non-prescription medicines as an essential part of self-care in European countries. Ultimately, this is also intended to enable health policy statements with regard to an efficient allocation of resources in outpatient care.Methods A simplified decision-analytical model is applied in which the self-purchase of a non-prescription medicine and a GP visit are considered as partial substitutes from the patient's perspective. In order to compare the decision paths of GP visit and self-medication in the sense of a cost-minimisation approach, the most relevant direct and indirect cost types are identified. Thirty countries are clustered following socioeconomic criteria. The value of self-medication is calculated for an individual MA case per Country Cluster, then the data is extrapolated to the entire population of countries and aggregated to a European value. Status quo and potential scenarios as well as relevant perspectives (patient, GP, healthcare system, national economy) are considered. Sensitivity analyses are conducted.Results Almost 1.2 billion MA cases are treated by self-medication in Europe p.a., saving EUR 26.31 billion in direct costs and EUR 10.41 billion in indirect costs (status quo). On average, one euro spent on OTC medicines by consumers saves national healthcare systems and economies EUR 6.70. 10–25% of current GP visits could be substituted by self-care, creating an additional savings potential of EUR 17.60 billion.Conclusion The study results reveal that self-medication in European countries is already associated with a high economic and social value for the individual and society. It is evident that current savings could be further increased by promoting self-care. Through responsible self-medication supported by an adequate health policy, resources and significant efficiency reserves for healthcare systems as well as national economies can be released. The resources freed up through an adequate self-care policy can play a significant role in building more resilient healthcare systems across Europe.
Keywords: self-care; self-medication; non-prescription medicine; public healthcare system; primary healthcare; decision-analytic model; minor ailment; Europe